2020
DOI: 10.1186/s40478-020-00941-6
|View full text |Cite
|
Sign up to set email alerts
|

RNA modifications in brain tumorigenesis

Abstract: RNA modifications are emerging as critical regulators in cancer biology, thanks to their ability to influence gene expression and the predominant protein isoforms expressed during cell proliferation, migration, and other pro-oncogenic properties. The reversibility and dynamic nature of post-transcriptional RNA modifications allow cells to quickly adapt to microenvironmental changes. Recent literature has revealed that the deregulation of RNA modifications can promote a plethora of developmental diseases, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 147 publications
0
13
0
Order By: Relevance
“…RNA m 6 A modification is an emerging field in the study of tumorigenicity and therapy resistance of glioma [ 7 , 11 , 27 , 32 ]. Our previous study also showed that the expression pattern of m 6 A ‘writers,’ ‘erasers,’ and ‘readers’ are highly associated with malignant progression and prognosis of glioma in both CGGA and TCGA cohorts [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA m 6 A modification is an emerging field in the study of tumorigenicity and therapy resistance of glioma [ 7 , 11 , 27 , 32 ]. Our previous study also showed that the expression pattern of m 6 A ‘writers,’ ‘erasers,’ and ‘readers’ are highly associated with malignant progression and prognosis of glioma in both CGGA and TCGA cohorts [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in understanding RNA N 6,2′- O -dimethyladenosine (m 6 A) modification have provided new insights into the molecular mechanism of malignant progression of diffuse gliomas [ 7 9 ]. Similar to DNA and protein modification, m 6 A is dynamically regulated by methyltransferases (‘writers’) and demethylases (‘erasers’) [ 10 , 11 ]. m 6 A can influence the entire RNA life cycle, including alternative polyadenylation, pre-RNA processing, RNA export from the nucleus to the cytoplasm, RNA translation, and RNA decay, through binding with different ‘readers’ of m 6 A [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serving as an epitranscriptomic layer of gene regulation, dynamic m 6 A modification has been demonstrated to play vital roles in a wide range of RNA metabolic processes ( Roignant and Soller, 2017 ; Yang et al , 2018 ; Shen et al , 2019 ; Huang et al , 2020 ). We found that although the global abundance and configuration of m 6 A were comparable between hybrid and parents, the number of genes harboring m 6 A sites was increased in the hybrid ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reversible RNA modifications, including N1-Methyladenosine (m 1 A), 5-Methylcytosine (m 5 C), and N6-Methyladenosine (m 6 A), have garnered substantial attention from oncologists in recent years [ 6 ]. Among these modifications, m 6 A is recognized as the most prevalent internal modification of poly-adenylated mRNAs and long non-coding RNAs in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%